Realistic vs romantic: the imagistic world of post-war English literature - Álvarez Calleja, María Antonia (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 1996)
The short story ¡s the genre which has come closest to representing the most poetic aspects of post-Second World War English literature, not only for its linguistic and stylistic concentration, but also for its imagistic world, in which the realistic contrasts with the romantic. Nevertheless, there is a transference from the classic literary images to a modern alternative. On the other hand, since 1945 writers have been preoccupied with the quest for self—a search for identity, an effort on the part of the heroes and heroines to understand and define who or what they are. In fact, the term identity plays a central role in virtually every judgment or opinion of the post-war literary scene.